Law Enforcement over Fishery Activities in Contested EEZs - Furuya, Kentaro (UI Scholars Hub, 2020)
The Exclusive Economic Zone (EEZ) was introduced with the adoption of the United Nations Convention on the Law of the Sea. In the vast waters extending from the baselines to 200 nautical miles, the Convention allows coastal States to enjoy sovereign rights over―fishing resources but has created delimitation issues with neighboring States. Law enforcement is vital to maintain fishery order for sustainable utilization of resources in EEZs, even in the contested maritime zones. Therefore, in this paper, the mechanism of law enforcement in the complicated contested maritime zone is described, taking the Japan-China Fisheries Agreement as an example of a possible practical solution.